The Insertion of the Tool Balanced Scorecard in the Strategic Planning of a Growing Company: A Case Study in the Company Metadil Metalúrgica Indústria e Comércio Ltda - Queiroz, Rafaela Thomaz (2015)
The aim of this study was to analyze how the Balanced Scorecard (BSC) can assist in the building the strategic planning of a small growing company, in order to achieve its strategic targets. For this purpose, it was carried out a study in a small company of the furniture segment, with a view to identify the benefits derived from the use of BSC at the organization. The following departments were analyzed: Human Resources, Marketing/Customers, Finances, and Production, and identified as BSC perspectives, they assisted in meeting the strategic targets of the company. In this study, it was adopted the qualitative methodology, with exploratory and descriptive nature, through case study. By the close analysis of BSC use, it was noticed, that there should be greater interaction among the different areas, with effective acting from HR area, regarding improvement in the company learning and growth, such as training and motivation programs; at the Production section, indicators were created in order to meet the increasing demand; concerning Marketing/Customers section, it was identified, through indicators at customers perspective, their real needs, in order to keep them satisfied with products and services; and, regarding to Finances, indicators were created to manage the investments and the minimization of production costs.